MINERALOGICAL -GEOCHEMICAL FEATURES AND AGE OF THORIUM-URANIUM MINERALIZATION IN PRECAMBRIAN OF THE UKRAINIAN SHIELD - SOMKA, V.; BONDARENKO, S.; STEPANIUK, L.; HRINCHENKO, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper discusses consideration of mineralogical-geochemical features of deposits and ore manifestations of potassium-uranium formation which are characterised by REE-Th-U mineralisation type. On an example of distribution of these ore manifestations of Ukrainian Shield the conclusion about formation of REE-Th-U mineralization over enough considerable large period of geological history, from Mesoarchean to Paleoproterozoic is made.